Faktor Penyebab Dampak Kecemasan Berbicara dalam Bahasa Inggris - Saniyya Dias; Ahmad Nidhom (Warmadewa Press, 2025)
English speaking anxiety is a common phenomenon among students and professionals. This study utilizes the Systematic Literature Review (SLR) method, drawing from Google Scholar, DOAJ, and Scopus (2013–2023). The results indicate that this anxiety is influenced by psychological factors (lack of self-confidence, fear of judgment), environmental factors (social pressure, lack of support), educational factors (teaching methods, lack of practice), linguistic factors (vocabulary limitations, pronunciation), and cultural factors (differences in social norms). These findings emphasize the importance of a holistic approach in addressing English speaking anxiety.